Analisis Pengembangan Jiwa Kewirausahaan di Kalangan Santri Pondok Pesantren - Amiruddin, Amiruddin (Universitas Negeri Makassar, 2025)
This study aims to analyze the factors influencing the development of entrepreneurial spirit among Islamic boarding school students, emphasizing the role of individual and environmental factors. Six independent variables were tested, including entrepreneurial motivation, self-efficacy, personal experience, family support, entrepreneurship education at the Islamic boarding school, and organizational experience. The study used a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method and involved 60 Islamic boarding school respondents selected through a purposive sampling technique. The results of the study indicate that all independent variables significantly influence the development of entrepreneurial spirit in students. The R² value of 0.682 indicates that 68.2% of the variation in entrepreneurial spirit development can be explained by the research model. Individual factors such as motivation, self-efficacy, and personal experience have been shown to increase students' readiness for entrepreneurship. Meanwhile, environmental factors, especially family support, Islamic boarding school entrepreneurship education, and organizational experience, have a strong influence, with family support being the most dominant factor. These findings confirm that the development of entrepreneurial spirit in students is the result of a synergy between internal and external factors. This research is expected to serve as a reference for Islamic boarding schools, families, and educational stakeholders in designing more effective entrepreneurship development programs for students.